25th Annual Martin J. Forman Memorial Lecture - Shah, Rajiv (2016)
Rajiv Shah MARTIN J. FORMAN MEMORIAL LECTURE Ending hunger: How leadership, data and technology can transform the global face of poverty 25th Annual Martin J. Forman Memorial Lecture JAN 7, 2016 - 05:15 PM TO 06:45 PM EST